PENGARUH PENGGUNAAN MULTI NUTRIENTS SAUCE (MNS) ERO II DALAM RANSUM TERHADAP PERTAMBAHAN BOBOT TUBUH SAPI POTONG - Sarina Karolina; Erwanto ,; Kusuma Adhianto (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This study aims to determine the effect of the use of Multi Nutrients Sauce (MNS) ERO II in the ration on feed consumption and average daily gain of beef cattle.  The research was conducted October 30th, 2015 - December 6th, 2015 at Ngudi Makmur farmer group, Mulyo Asri village, Tulang Bawang Tengah district, Tulang Bawang Barat regency. Samples ration was analysed at the Laboratory of Nutrition and Feed Science.  Department of Animal Husbandry, Faculty of Agriculture, University of Lampung.  The experimental design used was a randomized block design (CRD) with three treatments and four blocks. The treatments were: 1. Basal diet; 2. Basal diet + 10% MNS; and 3. Unila diets + 10% MNS. Result of experiment showed that the addition of MNS ERO II significantly affected (P<0.05) on consumption, and average daily gain of beef cattle. Keywords: Multi Nutrients Sauce, Feed Consumption, Average Daily Gain